Improving English Reading Comprehension Skills Through SQ4R Method - Lus Firdaus Zakiya (LP. Ma'arif Janggan Magetan, 2023)
This study aims to obtain data on the improvement of English reading comprehension skills through the SQ4R method for third grade students of MI Miftahus Sholah Mojokerto. The research subjects were third grade students in semester II of the 2022/2023 school year. This research was conducted using the Kemmis and Mc. Taggart model which was carried out with the stages of planning, implementation, observation, and reflection. The results of the research using the SQ4R method showed data obtained from the reading comprehension evaluation test of students who scored ≥ 75 in cycle I 55.55% and in cycle II obtained 83.33%. While monitoring teacher and student activities in cycle I the first meeting was 55% and the second meeting was 70%, while cycle II the first meeting was 85% and the second meeting was 90%. Thus reading comprehension with the SQ4R method can improve the reading comprehension skills of grade III students of MI Miftahus Sholah Mojokerto.